The impact of the SEC's regulation of non-GAAP disclosures - Heflin, Frank; Hsu, Charles (Journal of Accounting and Economics, 2008)
Rules implemented by the U.S. Securities and Exchange Commission in 2003 impose additional disclosure and filing requirements on firms publicly disclosing non-GAAP earnings. We find the regulations produced (1) modest declines in the frequency of special- and other-item exclusions, (2) a decline in exclusion magnitude, (3) a modest decline in the probability disclosed earnings meet or beat forecasts, and (4) a decline in the association between returns and forecast errors. Our results suggest that, while the regulations reduced firms’ use of non-GAAP disclosures to improve performance perceptions, they also reduced firms’ willingness to use non-GAAP earnings to convey permanent earnings.